Data from: Latest Ordovician (Hirnantian) brachiopod faunal lists used for non-matric multidimensional scaling (NMDS) and network analyses ... - Jin, Jisuo; Harper, David A. T. (Dryad, 2023)
A total of 107 brachiopod genera of Hirnantian age among 42 localities worldwide are compiled into a binary dataset (Table S1; presence =1, absence = 0). The majority of the faunal lists was derived from the well-screened Hirnantian brachiopod faunal data of Rong et al. (2020). In this study, the Hirnantian faunal lists are updated for the following localities: Anticosti Island, eastern Canada; Edgewood region, American Mid-Continent; Mackenzie Mountains, northwestern Canada. Detailed discussions on these faunal update and references are provided in the main paper (section on Paleobiogeography of the Mackenzie Mountains Hirnantian fauna). ... : The faunal list data were collected from the following sources: Taxonomic study of the Hirnantian brachiopods from the Mackenzie Mountains (this study). Taxonomic reassessment of Hirnantian-age brachiopods from Anticosti Island (eastern Canada) and the Edgewood region (American Mid-continent). Existing publications that reports Hirnantian-age brachiopods. The dataset consists of supplemental data from "Latest Ordovician (Hirnantian) brachiopod faunal lists used for non-matric multidimensional scaling (NMDS) and network analyses" (see Figs. 3 and 4 of main paper) ...